PEACE ACCORDING TO QUR'AN - Yani, Ahmad (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2021)
Peace is an important topic in Islam. The dynamics of Muslim’s life cannot be separated from this topic, particularly considering national and international political conflicts. The Qur'an has fully explained the concept of peace as well as the concept of war. This paper aims to explain Islamic teachings about the concept of peace and the concept of war which has been explained by the Qur'an and the Sunnah of the Prophet. Especially regarding the provisions of Jihad in Islam. The method used in this paper is the inductive method and the analytical method. The inductive method is used to collect all information related to the concept of peace in the Qur'an, the concept of war in the Qur'an, the provisions of jihad in the Qur'an and Hadith. The analytical method is used to define the concepts of Jihad and war in the Qur'an, explain the content and meaning of these verses, and analyze the contextualization of the concept of war in the Qur'an according to contemporary political dynamics. As a result of this research, the Qur'an has fully explained the concepts of peace and war. War in Islam is permissible under certain conditions. Islam also teaches that international peace of agreements should follow and established by Islamic law.